IMPACTS OF CLIMATE CHANGE AND VARIABILITY ON CROP PRODUCTION IN OYO STATE, SOUTH-WEST, NIGERIA - Adetayo, A.O.; Owolade, E.O.; Adeyeye, J.A.; Faloye, O.T.; Eruola, A.O. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study examined the impacts of climate change and variability on crop production in Oyo State, Nigeria. A systematic random sampling technique was used in selecting 240 respondents. Data were collected through the administration of questionare. Meteorological data were obtained from the archives of the Nigerian Meteorological Agency (NIMET) for a period of 35 years (1990-2024). Thirty-five years data on annual agricultural production were also collected from the State Agricultural Development Project (ADP) and the Central Bank (CBN) agricultural annual survey. The results obtained from the study showed that climate change does have a significant effect on crop production in the study area, as most farmers interviewed have noticed significant changes in the climatic conditions as manifested in different forms. There are positive correlations between climatic characteristics and the yield of crops. Pearson’s Product Correllaton Coefficient (r) for maize, cowpea, okro, sorghum, melon and pepper are 0.51, 0.50, 0.12, 0.30, 0.26 and 0.20 respectively at p ≤ 0.05. The mean rainfall cessation, length of raining season and rainfall onset are 320.14th day, 235.31days and 91.63th day respectively. Based on rainfall distribution pattern observed the study recommends that farmers should switch to crop varieties that would be accommodated by the present annual amount and duration of growing season.